Propionate and Alzheimer’s Disease - Killingsworth, Jessica; Sawmiller, Darrell; Shytle, R. Douglas (Frontiers in Aging Neuroscience, 2021)
Propionate, a short chain fatty acid, serves important roles in the human body. However, our review of the current literature suggests that under certain conditions excess levels of propionate may play a role in Alzheimer’s disease (AD). The cause of the excess levels of propionate may be related to the Bacteroidetes phylum, which are the primary producers of propionate in the human gut. Studies have shown that the relative abundance of the Bacteroidetes phylum are significantly increased in older adults. Other studies have shown that levels of the Bacteroidetes phylum are increased in persons with AD. Studies on diet, medication use, and propionate metabolism offer additional potential causes. There are many different mechanisms by which excess levels of propionate may lead to AD, such as hyperammonemia. These mechanisms offer potential points for intervention.